Confederate citadel : Richmond and its people at war - DeCredico, Mary A. (New directions in southern history., 2020)
Richmond, Virginia: pride of the founding fathers, doomed capital of the Confederate States of America. Unlike other Southern cities, Richmond boasted a vibrant, urban industrial complex capable of producing crucial ammunition and military supplies. Despite its northern position, Richmond became the Confederacy's beating heart -- its capital, second-largest city, and impenetrable citadel. As long as the city endured, the Confederacy remained a well-supplied and formidable force. But when Ulysses S. Grant broke its defenses in 1865, the Confederates fled, burned Richmond to the ground, and surrendered within the week. This book offers a detailed portrait of life's daily hardships in the rebel capital during the Civil War. Here, barricaded against a siege, staunch Unionists became a dangerous fifth column, refugees flooded the streets, and women organized a bread riot in the city. Drawing on personal correspondence, private diaries, and newspapers, the author spotlights the human elements of Richmond's economic rise and fall, uncovering its significance as the South's industrial powerhouse throughout the Civil War.